2012
DOI: 10.1002/jmri.23682
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MRI and 18F‐NaF PET/CT in patients with patellofemoral pain

Abstract: Purpose To determine whether bone metabolic activity corresponds to bone and cartilage damage in patients with patellofemoral pain. Materials and Methods We acquired MRI and 18F-NaF PET/CT scans of the knees of 22 subjects. We compared locations of increased tracer uptake on the 18F-NaF PET images to bone marrow edema and cartilage damage visualized on MRI. Results We found that increased bone activity on 18F-NaF PET does not always correspond to structural damage in the bone or cartilage as seen on MRI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Although cartilage is aneural, the subchondral bone is richly innervated, and elevated cartilage/bone mechanical stress has long been proposed to be a possible cause of pain (28). Immunohistochemistry and confocal microscopy studies confirm the sensory and sympathetic innervation of bone and its potential role in skeletal pain (26) and our recent study using F-NaF positron emission tomography showed that chronic patellofemoral pain patients display elevated bone metabolic activity (15). However, testing a hypothesis that relates joint pain to mechanical stress remains difficult due to an inability to measure stress in vivo and the subjective assessment of pain.…”
Section: Introductionmentioning
confidence: 55%
“…Although cartilage is aneural, the subchondral bone is richly innervated, and elevated cartilage/bone mechanical stress has long been proposed to be a possible cause of pain (28). Immunohistochemistry and confocal microscopy studies confirm the sensory and sympathetic innervation of bone and its potential role in skeletal pain (26) and our recent study using F-NaF positron emission tomography showed that chronic patellofemoral pain patients display elevated bone metabolic activity (15). However, testing a hypothesis that relates joint pain to mechanical stress remains difficult due to an inability to measure stress in vivo and the subjective assessment of pain.…”
Section: Introductionmentioning
confidence: 55%
“…Recently, imaging data from patients with PFP have been published using newer imaging modalities and technologies in hope that these modalities are more sensitive to detect any possible pathology related to the cartilage under the patella and in the patellar groove. Positron emission tomography-computed tomography (PET-CT) imaging shows that 44-85 % of older adults (mean age [29][30][31][32][33][34] with PFP show increased tracer uptake in the patellofemoral joint that tends to coincide with bone marrow oedema, subchondral bone cysts, and cartilage damage [45][46][47]. Furthermore, there appears to be an association between the tracer uptake and pain intensity, and an association between pain location and location of tracer uptake that suggests an aetiological link [46].…”
Section: Patellofemoral Pain and Pathology?mentioning
confidence: 99%
“…According to recent studies, 18 F-FDG PET sensitively detects active inflammation in rheumatic diseases, including synovitis in RA [12][13][14][15][16][17][18]. In contrast, 18 F-NaF PET is an increasingly used molecular imaging modality in human skeletal disorders [19][20][21][22][23]. 18 F-NaF incorporates into the bone at the site of bone formation or remodeling; there, osteoblasts and osteoclasts are activated, and 18 F ions exchange the hydroxyl ions in bone crystal to form fluorapatite.…”
Section: Introductionmentioning
confidence: 95%